Open versus minimally-invasive surgical techniques in pediatric renal tumors: A population-level analysis of in-hospital outcomes. Issue 4 (August 2021) - Simmons, Kirsten L.; Chandrapal, Jason C.; Wolf, Steven; Rice, Henry E.; Tracy, Elisabeth E.; Fitzgerald, Tamara; Pomann, Gina-Maria; Routh, Jonathan C.
Summary: Introduction: Minimally-invasive surgery (MIS) has been adopted slowly in pediatric oncology. We attempted to describe contemporary national trends in MIS use; we hypothesized that adolescents (who are more likely to have relatively small renal cell carcinomas) would have a higher proportion of MIS than younger children (who are more likely to have relatively large Wilms tumors) and that this relationship would vary by region. Objective: To explore whether pediatric urologic oncology outcomes vary by patient age or by surgical technique. Methods: We queried the 1998–2014 National Inpatient Sample (NIS) and included encounters in children aged ≤ 18 y, ICD-9 diagnostic code for renal tumor, and procedure code for open or MIS partial or radical nephrectomy. All analyses used weighted descriptive statistics and outcomes are compared based on age group (</>10 y) or surgery type; Wald-Chi square test was used for differences in proportions and unadjusted weighted ANOVA was used to test for differences in means. Results: 9259 weighted encounters were included; 91% were <10 years old and 50.7% were female. MIS surgery accounted for 1.8% of encounters; there was a difference in proportions by age group (1% <9 y vs. 9.9% >9 y, p < 0.01). The proportion of surgery type was similar across regions within age groups, however. Complications occurred in 13.3% of encounters; mean inpatient length of stay was 8.9 days (SD: 0.3); mean cost was $ 34, 457.68 (SD: $1197.00). There was no evidence of a difference between surgery type and proportion of post-operative complications, mean inpatient length of stay or mean inpatient cost. Discussion: The admission-based, retrospective design of NIS left us unable to assess long-term outcomes, repeated admissions, or to track a particular patient across time; this is particularly relevant for oncologic variables on interest such as tumor stage or event-free survival. We were similarly limited in evaluating the effect of pre-surgical referral patterns on patient distributions. Conclusion: In this preliminary descriptive analysis, MIS techniques were infrequently used in children, but there was a higher proportion of MIS use among adolescents. There were similar proportions of surgery type across geographic regions within the United States. Whether this infrequent usage is appropriate is as yet unclear given the lack of Level I evidence regarding the relative merits of MIS and open surgery for pediatric and adolescent renal tumors.